A Conceptual Middleware for Adaptive Sanctioning in Normative Multi-Agent Systems - Lima, Igor Conrado Alves de; Nardin, Luis Gustavo; Sichman, Jaime Simão (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2016: Anais do X Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2016.33213, 2016)
The use of the normative approach to govern Multi-Agent Systems has been motivated by the increasing interest in balancing between agents’ autonomy and global system control. In Normative Multi-Agent Systems (NMAS), despite the existence of norms specifying the rules of how agents ought or ought not to behave, agents have the autonomy to decide whether or not to act in compliance with them. A suitable way to govern agents is using sanction-based enforcement mechanisms. These mechanisms provide agents with a certain level of autonomy while controlling them through the application of sanctions. Here we present a conceptual middleware that makes use of an adaptive sanctioning enforcement model to improve the level of norm compliance in NMAS by enabling agents to choose among several categories of sanctions.